Cross-Cultural Perspectives on Brand Experience and Purchase Intention: A Systematic Literature Review - Marhadi, Marhadi; Bakytbekovna, Aiupova Nurgul; Taralik, Krisztina (Acta Carolus Robertus, 2024)
In the last several years, there has been significant research on how cross-cultural perceptions affect brand experience and purchase intention. With an emphasis on the drivers, dynamics, and management methods involved, this systematic literature review attempts to provide an overview of the existing literature on customer experience and its impact on purchase intention. This review examines the influence of brand experience on purchase intention or willingness to buy in cross-country contexts. It focuses on the relationship between brand experience and purchase intention, exploring the factors that shape this relationship and the mechanisms through which it operates. The goal of this study is to provide an exhaustive analysis and synthesis of the academic literature on brand experience. To accomplish this, the researchers conduct a systematic review, finding and evaluating 73 appropriate articles from 38 journals. The analysis covers significant information concerning empirical versus conceptual studies, industry focus, country of study, research design, data analysis methods, and characteristics of respondents. Our understanding of the connection between brand experience and purchase intention in cross-country scenarios is enhanced by the findings of these studies. They highlight the complex nature of the ’country image’ concept and the importance of considering both cognitive and emotive factors when shaping consumer perceptions and beliefs. Overall, this systematic evaluation of the literature provides insights into how brand experience influences consumers’ propensity or intention to make global purchases. The results emphasize the critical importance of understanding the complex relationship between country image and consumer behavior. These insights can assist firms in customizing their brand experiences to various cultural contexts and in informing marketing strategies.